2018
DOI: 10.4103/jcvjs.jcvjs_81_18
|View full text |Cite
|
Sign up to set email alerts
|

Ability of magnetic resonance imaging to accurately determine alar ligament integrity in patients with atlanto-occipital injuries

Abstract: Objective:The objective of this study is to evaluate the the reliability of magnetic resonance imaging (MRI) in diagnosing alar ligament disruption in patients with potential atlanto-occipital dissociation (AOD).Materials and Methods:Three-blinded readers performed retrospective review on 6 patients with intra-operative confirmed atlanto-occipital dissocation in addition to a comparison cohort of patients with other cervical injuries that did not involve the atlanto-occipital articulation. Ligament integrity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…Secondly, the importance of the alar ligaments in maintaining CCJ stability necessitates direct inspection of these ligaments on all cervical MRI examinations in the acute trauma setting. Given the relatively small size of the alar ligament, anatomic complexity of the CCJ, and potential for motion and artifact degraded imaging in the trauma setting, direct inspection of the alar ligaments may be challenging [ 17 - 19 ]. However, specifically-tailored MRI protocols in the setting of clinical or radiologic suspicion for CCJ injury, including both coronal T2-weighted imaging and multiplanar imaging, may help mitigate these challenges [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the importance of the alar ligaments in maintaining CCJ stability necessitates direct inspection of these ligaments on all cervical MRI examinations in the acute trauma setting. Given the relatively small size of the alar ligament, anatomic complexity of the CCJ, and potential for motion and artifact degraded imaging in the trauma setting, direct inspection of the alar ligaments may be challenging [ 17 - 19 ]. However, specifically-tailored MRI protocols in the setting of clinical or radiologic suspicion for CCJ injury, including both coronal T2-weighted imaging and multiplanar imaging, may help mitigate these challenges [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reliability and benefits of MRI in excluding alar ligament injuries are disputable. With use of intraoperative correlation, Dyas et al (35) revealed that MRI is imperfect in depicting upper cervical ligament injuries in patients with atlanto-occipital dissociation due to inconsistent and unsatisfactory inter-and intraobserver reliability. They concluded that standardized algorithms are needed for the use of MRI and interpretation of MRI findings.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the last decades, the gradual technological improvement has been followed by the introduction of novel diagnostic radiological criteria for atlantooccipital dislocation (AOD), as for example the condylar sum (Fig. 1 a–c) [ 4 , 15 ]. Historically, this life-threatening traumatic injury of the CVJ was diagnosed on X-rays or regular CT-scan.…”
Section: Novelties For Safer Cvj Surgerymentioning
confidence: 99%